Finely designed medium-band-gap polymer donor with judiciously selecting chalcogen atom for high efficiency polymer solar cell. (June 2017) - Gong, Xue; Feng, Shiyu; Li, Guangwu; Hou, Ran; Liu, Yahui; Zhang, Zhe; Li, Cuihong; Bo, Zhishan
Abstract: A novel medium band gap copolymer (PBO ) based on benzodithiophene (BDT) and benzoxadiazole (BOz) was synthesized and applied in polymer solar cells (PSCs). The introduction of two alkylthio side chains onto the BDT unit can endow the resulting polymer (PBO ) with good solubility in solutions and good crystallinity in the solid state. The low HOMO level of −5.52 eV and the broad absorption ranging from 350 to 700 nm makePBO a promising donor material for PSCs. Power conversion efficiency higher than 7% has been achieved for devices usingPBO as the donor material and PC71 BM orITIC as the acceptor material. Graphical abstract: A novel medium band gap copolymer (PBO ) based on benzodithiophene (BDT) and benzoxadiazole (BOz) was synthesized by judiciously selecting chalcogen atom and applied in polymer solar cells (PSCs). Power conversion efficiency higher than 7% has been achieved by usingPBO as the donor and PC71 BM orITIC as the acceptor. Highlights: A novel polymer (PBO ) comprising alkylthiophenyl substituted BDT and BOz was synthesized. PBO possesses deep HOMO energy level and medium band gap. PCE higher than 7% was achieved forPBO :PC71 BM orPBO :ITIC based devices.